2022
DOI: 10.1111/odi.14209
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial–mesenchymal transition and cancer stem cells: A route to acquired cisplatin resistance through epigenetics in HNSCC

Abstract: Chemoresistance is associated with tumor recurrence, metastases, and short survival. Cisplatin is one of the most used chemotherapies in cancer treatment, including head and neck squamous cell carcinoma (HNSCC), and many patients develop resistance. Here, we established cell lines resistant to cisplatin to better understand epigenetics and biological differences driving the progression of HNSCC after treatment. Cisplatin resistance was established in CAL‐27 and SCC‐9 cell lines. Gene expression of HDAC1, HDAC2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 69 publications
2
8
0
Order By: Relevance
“…More importantly, our scATAC sequencing revealed that cluster 1 displayed enriched peaks with transcriptional motifs containing stem-cell like features, EMT surface markers, and high expression of KNC genes such as AKR1C1, AKR1C2, AKR1C3 and SPP1. These findings are supported by a recent study which demonstrated that EMT and cancer stem cells lead to acquired CDDP resistance and tumor recurrence through epigenetic changes in HNSCC (57). Although our data suggest that a unique epigenomic reprogramming contributes to evolution of CDDP-resistant clones in HNSCC, it remains unclear how this occurs and therefore further in vitro and in vivo molecular characterization is necessary to understand this mechanistic link.…”
Section: Discussionsupporting
confidence: 84%
“…More importantly, our scATAC sequencing revealed that cluster 1 displayed enriched peaks with transcriptional motifs containing stem-cell like features, EMT surface markers, and high expression of KNC genes such as AKR1C1, AKR1C2, AKR1C3 and SPP1. These findings are supported by a recent study which demonstrated that EMT and cancer stem cells lead to acquired CDDP resistance and tumor recurrence through epigenetic changes in HNSCC (57). Although our data suggest that a unique epigenomic reprogramming contributes to evolution of CDDP-resistant clones in HNSCC, it remains unclear how this occurs and therefore further in vitro and in vivo molecular characterization is necessary to understand this mechanistic link.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, in our A549CisR cell line, cisplatin resistance manifests as ongoing EMT, indicated by upregulation of N-cadherin and repression of E-cadherin, which substantially increased migratory potential. Previous studies have also noted a similar co-existence between cisplatin resistance and EMT induction [ 72 , 74 ]. Importantly, our derived A549CisR cell line, representing an EMT phenotype, demonstrated ABCC1 and ABCC4 upregulation and ABCG2 downregulation; this relationship was observed for GSE108214, while ABCG2 repression has also been noted in advanced colorectal cancer cells undergoing EMT and patient samples [ 57 ].…”
Section: Discussionsupporting
confidence: 61%
“…(Lima de Oliveira et al, 2022). Our results suggest that the upregulation of HDAC1 and SIRT1 in the CisR cell lines can be mediated by the TNF-alpha/NFkB signaling.…”
Section: Tnf-alpha/nfkb Signaling Pathway Is Upregulated In Oscc With...mentioning
confidence: 62%